Glycogenosis is common in nonalcoholic fatty liver disease and is independently associated with ballooning, but lower steatosis and lower fibrosis. (7th January 2021) - Allende, Daniela S; Gawrieh, Samer; Cummings, Oscar W; Belt, Patricia; Wilson, Laura; Van Natta, Mark; Behling, Cynthia A; Carpenter, Danielle; Gill, Ryan M; Kleiner, David E; Yeh, Mathew M; Chalasani, Naga; et al.
Abstract: Background/Aims: Glycogen synthesis and storage are normal hepatocyte functions. However, glycogenosis, defined as excess hepatocyte glycogen visible by routine H&E light microscopy, has not been well characterized in nonalcoholic fatty liver disease (NAFLD). Methods: Glycogenosis in NAFLD liver biopsies was graded as "none", "focal" (in <50% of hepatocytes), or "diffuse" (in ≥50% of hepatocytes). Clinical and pathological variables associated with glycogenosis were assessed. 2047 liver biopsies were prospectively analysed. Results: In adults and children, any glycogenosis was present in 54% of cases; diffuse glycogenosis was noted in approximately 1/3 of cases. On multiple logistic regression analysis, adults with glycogenosis tended to be older ( P  = .003), female ( P  = .04), have higher serum glucose ( P  = .01), and use insulin ( P  = .02). Adults tended to have lower steatosis scores ( P  = .006) and lower fibrosis stages ( P  = .005); however, unexpectedly, they also tended to have more hepatocyte injury including ballooning ( P  = .003). On multiple logistic regression analysis, paediatric patients with glycogenosis were more likely to be Hispanic ( P  = .03), have lower body weight ( P  = .002), elevated triglycerides ( P  = .001), and a higher fasting glucose ( P  = .007). Paediatric patients with glycogenosis also had less steatosis ( P  < .001) than those without. Conclusions: Glycogenosis is common in adult and paediatric NAFLD, and is associated with clinical features of insulin resistance. Glycogenosis is important to recognize histologically because it may be misinterpreted as ballooning, and when diffuse, confusion with glycogen storage disorders or glycogenic hepatopathy must be avoided. The newly observed dichotomous relationship between glycogenosis and increased liver cell injury but decreased steatosis and fibrosis requires further study.